2022
DOI: 10.1021/jacs.2c06579
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Lateral Flow Device for Biosensing

Abstract: Many biosensing methods rely on signals produced by enzyme-catalyzed reactions and efficient methods to detect and record this activity. Herein, we report a wireless lateral flow device and demonstrate the conversion of oxidase reactions to changes in the resonance of radio frequency identification (RFID) circuits. The detection is triggered by polyoxometalate-catalyzed oxidative doping of polypyrrole (pPy) when exposed to oxidase-generated H2O2. We have integrated this transduction and RFID capability into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…144 More importantly, they integrated the carboxylate-functionalized PPy core–shell nanoparticles (PPyNPs) with the radio frequency identification (RFID) circuits to create a portable, low-cost and rapid bioelectronic device. 145 The electrical conductivity of carboxylate-functionalized PPyNPs (Fig. 12A) could decrease when exposed to oxidase-generated H 2 O 2 .…”
Section: Advanced Bioelectronic Devicesmentioning
confidence: 98%
“…144 More importantly, they integrated the carboxylate-functionalized PPy core–shell nanoparticles (PPyNPs) with the radio frequency identification (RFID) circuits to create a portable, low-cost and rapid bioelectronic device. 145 The electrical conductivity of carboxylate-functionalized PPyNPs (Fig. 12A) could decrease when exposed to oxidase-generated H 2 O 2 .…”
Section: Advanced Bioelectronic Devicesmentioning
confidence: 98%
“…The polypyrrole shell allows for further functionalization of the particle surfaces, via a reductive conjugate addition to the deprotonated form of doped polypyrrole, 6,7 which we have found has broad utility in tailoring the properties of polypyrrole for specific applications. 8 We hypothesized that functionalization would enhance the extractive capabilities of our particles by the incorporation of supramolecular hosts, such as β-cyclodextrin (β-CD), 9,10 which are well known to interact with aromatic compounds via their hydrophobic cavities. 11,12 Herein, we present our results on the formation of pPy colloidal particles containing β-cyclodextrin and the use of these materials for the extraction of various aromatic compounds from water.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In our previous studies, we found that these particles can be loaded with various organic dyes, suggesting their potential for extracting organic molecules from solution. The polypyrrole shell allows for further functionalization of the particle surfaces, via a reductive conjugate addition to the deprotonated form of doped polypyrrole, , which we have found has broad utility in tailoring the properties of polypyrrole for specific applications . We hypothesized that functionalization would enhance the extractive capabilities of our particles by the incorporation of supramolecular hosts, such as β-cyclodextrin (β-CD), , which are well known to interact with aromatic compounds via their hydrophobic cavities. , …”
Section: Introductionmentioning
confidence: 99%
“…A majority of studies have combined SERS with the paper-based lateral flow assay (LFA) – the most widely used point-of-care (POC) diagnostic format that could clinically analyze free proteins or exosomal proteins in complex matrices such as saliva, urine, whole blood. In the LFA biosensors, the capillary forces drive the lateral flow of the clinical liquid samples containing analytes along the surface of the nitrocellulose (NC) membrane. The main merits of LFA include low cost, fast result readout, simplicity, and ease-to-use; however, one major hurdle of the LFA platform is the limited multiplexing capability due to its in-line design geometry. , A few LFA biosensors have been reported for multiplexed detection of proteins, but they usually suffer from cross-reactivity and false-negative results due to the hook effect, and measure at most two protein biomarkers. These inherent drawbacks compromise the diagnostic accuracy of LFA. Therefore, there is an urgent need to develop alternative high-throughput POC strategies enabling quantitative detection of a panel of exosomal proteins for cancer liquid biopsies.…”
mentioning
confidence: 99%
“…The main merits of LFA include low cost, fast result readout, simplicity, and ease-touse; however, one major hurdle of the LFA platform is the limited multiplexing capability due to its in-line design geometry. 40,41 A few LFA biosensors have been reported for multiplexed detection of proteins, but they usually suffer from cross-reactivity and false-negative results due to the hook effect, and measure at most two protein biomarkers. 42−45 These inherent drawbacks compromise the diagnostic accuracy of LFA.…”
mentioning
confidence: 99%